Pengembangan Aplikasi Penerimaan Mahasiswa Baru Berbasis Android Dilengkapi dengan Fitur Push Notification - Erliyah Nurul Jannah; Dwi Khusnul Bayturrohman; Endang Kurniawan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Student Admission is an annual compulsory activity which is always conducted by universities, both state university and private university. Student admission information is usually disseminated through a website, including registration information, test schedule, test location, and test result. This kind of publication requires prospective students to always monitor the pages of student admission site for checking whether there is new information or not. If prospective students do not always monitor the web, they may not getting the latest information, especially if there is a change of schedule information, location, or test result. Therefore, it is necessary to build an Androidbased student admission application by applying push notification feature. Application is built through the stages of requirement analysis, design, implementation, and testing. The test results show that Android-based student admission application is able to serve as student enrollment media. In addition, the application is also able to convey the latest information related to student admission in real time. Thus, prospective students do not need to always access the web for obtaining latest information.